2023
DOI: 10.3390/w15223931
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model of Residual Soil Shear Strength under Dry–Wet Cycles and Its Uncertainty

Jiefa Ding,
Shijun Wang,
Haoran Huang
et al.

Abstract: Granite residual soil is widely distributed in Southeast Fujian. Large-scale engineering construction leads to the exposure of residual soil slopes to the natural environment. Affected by seasonal climate factors, the soil of slopes experiences a dry–wet cycle for a long time. The repeated changes in water content seriously affect the shear strength of soil, and then affect the stability of the slope. In order to explore the influence of the dry–wet cycle on the shear strength of granite residual soil in Fujia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been shown that the shear strength of soil after F-T cycles is an important index to reflect the mechanical properties of soil and describe the characteristics of soil after F-T cycles [12][13][14], and the shear strength parameters of soil mainly includes the cohesion and internal friction angle of soil [15][16][17][18][19][20]. According to relevant research results at home and abroad, through conducting F-T cycle tests on different types of soil, it is shown that there are significant differences in the variation law of soil shear strength, which is characterized by an increase, decrease, and basically unchanged variation law of soil shear strength with an increasing number of F-T cycles [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the shear strength of soil after F-T cycles is an important index to reflect the mechanical properties of soil and describe the characteristics of soil after F-T cycles [12][13][14], and the shear strength parameters of soil mainly includes the cohesion and internal friction angle of soil [15][16][17][18][19][20]. According to relevant research results at home and abroad, through conducting F-T cycle tests on different types of soil, it is shown that there are significant differences in the variation law of soil shear strength, which is characterized by an increase, decrease, and basically unchanged variation law of soil shear strength with an increasing number of F-T cycles [6,12].…”
Section: Introductionmentioning
confidence: 99%